Comparison of Palivizumab-Like Antibody Binding to Different Conformations of the RSV F Protein in RSV-Infected Adult Hematopoietic Cell Transplant Recipients. (22nd January 2018) - Ye, Xunyan; Iwuchukwu, Obinna P; Avadhanula, Vasanthi; Aideyan, Letisha O; McBride, Trevor J; Ferlic-Stark, Laura L; Patel, Kirtida D; Piedra, Felipe-Andres; Shah, Dimpy P; Chemaly, Roy F; Piedra, Pedro A
Abstract: Background: Most respiratory syncytial virus (RSV) vaccine candidates include fusion (F) protein in different conformations. Antigenic site II found in the different F conformations is the target of palivizumab, the only US Food and Drug Administration approved monoclonal antibody (mAb). Serum palivizumab-like antibody (PLA) is a potential serologic correlate of immunity. Our objective was to determine if different conformations of F protein in a palivizumab competitive antibody (PCA) assay affect the PLA concentrations. Methods: Four PCA assays were standardized using mAbs. Each contained prefusion, postfusion, or intermediate F forms. PLA concentrations were measured in acute and convalescent sera from 22 RSV/A and 18 RSV/B-infected adult hematopoietic cell transplant (HCT) recipients. PLA concentrations were calculated using a 4-parameter logistic regression model and analyzed for statistical significance. Results: PCA assays revealed significantly greater PLA concentrations in convalescent sera; comparable increases in PLA concentration in RSV/A and RSV/B-infected HCT recipients; and significantly reduced PLA concentrations in HCT recipients who shed RSV ≥14 days. A significant positive correlation was observed between PCA assays and RSV neutralizing antibody titers. Conclusions: F protein conformation does not appear to have a measurable impact on PCA assays for measuring PLA induced by RSV/A or RSV/B infection. Abstract : The RSV F protein conformation did not have a measurable impact on the palivizumab competitive antibody assay performance for measuring palivizumab-like antibody (PLA) in RSV-infected patients, and PLA might serve as an immune correlate of protection against RSV infection.